THE EFFECT OF PROFIT AND LEVERAGE MANAGEMENT ON STOCK RETURN: (Study on Manufacturing Companies Listed on the Indonesia Stock Exchange in 2018-2020) - Yermiana, Vaskha; Nasirwan, Nasirwan; Situmeang, Chandra (Teunuleh Publisher, 2022)
This study aims to examine and analyze the effect of Profit Management and Leverage on Stock Returns. The research was conducted on manufacturing sector companies listed on the Indonesia Stock Exchange (IDX) with an observation period from 2018-2020. The testing of this research model is based on agency theory and signaling theory. The research population consisted of 194 companies using purposive sampling and obtained 67 companies with 201 observations. Data analysis technique using Multiple Linear Regression Analysis. This study obtains empirical evidence, namely: First, Earnings Management has a significant negative effect on stock returns. Second, Leverage has a significant negative effect on stock returns. These results indicate that agency theory and signal theory are supported in this research model.